Approximate Analytical Solution of Liner Boundary Value Problems by Laplace-Differential Transform Method - Kumari, Kiranta; Shanker, Gauree; Gupta, Praveen Kumar (Journal of Informatics and Mathematical Sciences, 2015)
In this paper, we study the approximate analytical solutions of homogeneous and non-homogeneous linear PDEs with boundary conditions by using the Laplace Differential Transform method (LDTM). For this purpose, we consider three illustrations with one Dirichlet and two Neumann boundary conditions and obtain the corresponding approximate analytical solutions. This method is capable of greatly reducing the size of computational domain and a few numbers of iterations are required to reach the closed form solutions as series expansions of some known functions.